PENGEMBANGAN E-LKPD BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI PERJUANGAN MASA PENJAJAHAN BELANDA DAN JEPANG PADA KELAS V SD - Mahemba, Klementina R; Sulistyowati, Prihatin; Yulianti, Yulianti (Wahana Sekolah Dasar, 2023)
The purpose of this study was to determine: the development, feasibility, practicality, and effectiveness of CTL-based E-LKPD in Grade V Elementary School. This research method is a development research using the ADDIE model with 5 stages, namely: Analysis, Design, Development, Implementation, Evaluation. The test subjects in this study were fifth grade students at SDN Bandungrejosari 1 Malang. The data collection instrument used a questionnaire. The data analysis technique used descriptive qualitative and quantitative. CTL-Based E-LKPD based on the results of validity by material experts obtained a score of 90% with a very valid category. The validity assessment by media experts obtained a score of 87% with a very valid category. The assessment of validity by linguists obtained a score of 90% in the Very valid category. The results of the teacher's questionnaire obtained 88% practicality in the very practical category. The results of the pre-test or initial test are 20% while the last post-test is 86.66% It can be ascertained that the CTL-based E-LKPD is valid for use in the classroom.